2017
DOI: 10.1163/1568539x-00003444
|View full text |Cite
|
Sign up to set email alerts
|

Structural, temporal and genetic properties of social groups in the short-lived migratory bat Nyctalus leisleri

Abstract: Social groups of bats that operate under fission–fusion dynamics tend to establish and maintain non-random associations. We examined the social and genetic structure of the Leisler’s bat (Nyctalus leisleri), a species that is typical of tree-dwelling and long-distance migratory species in Europe. We used long-term co-occurrence data (capture-recapture sampling of roosting individuals) in combination with individual genetic relatedness (inferred from a set of microsatellite markers) to assess relationships betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…It is important to add that occasions of social grooming occurred strictly among members of the same social groups (Kozhurina, 1993). A more recent study of the temporal and genetic components of associative dynamics in Nyctalus leisleri also found a stronger impact of cohort year on the composition of social groups inferred through network analysis (Naďo et al, 2017). As pointed out by the authors, although genetic relatedness was also observed to significantly impact association between dyads, this could be the result of different genetic profiles between cohorts due to male-biased gene flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to add that occasions of social grooming occurred strictly among members of the same social groups (Kozhurina, 1993). A more recent study of the temporal and genetic components of associative dynamics in Nyctalus leisleri also found a stronger impact of cohort year on the composition of social groups inferred through network analysis (Naďo et al, 2017). As pointed out by the authors, although genetic relatedness was also observed to significantly impact association between dyads, this could be the result of different genetic profiles between cohorts due to male-biased gene flow.…”
Section: Discussionmentioning
confidence: 99%
“…Studies monitoring roost associations have shown females will roost preferentially with some females rather than others, resulting in a non-random association pattern within the colony (e.g. Willis & Brigham, 2004;Metheny et al, 2008;Patriquin et al, 2013;Naďo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For roost switching simulations, we designed an area of 128.2 ha (~ 900 × 1800 m) with a 3-dimensional configuration identical to habitat conditions in the field (x, y coordinates and z heights of 944 cavities available for roosts). This simplified habitat setting was considered sufficient because cavity density and height are the primary determining factors in roost-site selection of tree-dwelling bats 6,10,11,25,54 . In a hexagonal grid divided into 37 equal cells, density of cavities ranged from 8 to 92 per a cell ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Groups roosting in tree cavities in Gavurky were found by radio-tracking or by search during dawn swarming with the help of a bat detector, and they were censused at evening emergence, supplemented by harp-trapping and individual banding. During long-term field observation from 2003 to 2014, we collected data on spatial distribution of bats’ roosts, group size, elevation of cavity entrance above the ground (hereafter cavity or roost height) and distance travelled during group roost switching (for details see 35 , 36 , 51 54 ). All methods were carried out in accordance with relevant guidelines and regulations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation